2020 IEEE International Conference on Engineering, Technology and Innovation (ICE/ITMC) 2020
DOI: 10.1109/ice/itmc49519.2020.9198540
|View full text |Cite
|
Sign up to set email alerts
|

Employing digital twins within production logistics

Abstract: Digitalisation and automation of existing processes are key competitive factors for industry. Still, logistic operations often comprise manual effort, because the movement of goods and material places stringent requirements on the interactions between different systems, human-computer/robot-interaction as well as on changes in the operative processes. In general, the introduction and uptake of new enabling technologies, like the IoT, in complex systems evolved over decades, are challenging. The experience has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For example, the study reported in [15] shows that creating a complete DT system for production lines enables machines to perform routine inspections without stopping while identifying any faulty parts. Meanwhile, DT systems can facilitate real-time analysis of manufacturing processes; as Hauge et al [16] show the role of digital twins in providing insight into errors and inefficiencies on production lines, thus reshaping the way manufacturers manage their operations.…”
Section: Related Workmentioning
confidence: 99%
“…For example, the study reported in [15] shows that creating a complete DT system for production lines enables machines to perform routine inspections without stopping while identifying any faulty parts. Meanwhile, DT systems can facilitate real-time analysis of manufacturing processes; as Hauge et al [16] show the role of digital twins in providing insight into errors and inefficiencies on production lines, thus reshaping the way manufacturers manage their operations.…”
Section: Related Workmentioning
confidence: 99%
“…The paper [ 40 ] discusses the use of digital twins to support decision-making in workstation design and logistics operations. The digital twin was developed using Unity and simulation software IPS and was tested in a production logistics testbed that included physical devices, an IoT infrastructure, and simulation software.…”
Section: Related Workmentioning
confidence: 99%
“…The concept is tested in a laboratory environment and the game engine Unity is used as a virtual environment to create the VM. Applications for workstation design by using IMMA (Intelligent Moving Manikins), for picking processes, routing, education, and monitoring are described; service systems need to be implemented and more experiments are necessary to evaluate the potential benefits of this approach [38]. Nevertheless, predefined control mechanisms can lead to suboptimal results, and, in the case of material flow systems, long waiting times and wasted energy may be the result.…”
Section: Decentralized Applicationsmentioning
confidence: 99%